Correction: Generality of toxins in defensive symbiosis: Ribosome-inactivating proteins and defense against parasitic wasps in Drosophila - Ballinger, Matthew J.; Perlman, Steve J. (PLoS pathogens, 2025)
[This corrects the article DOI: 10.1371/journal.ppat.1006431.].